Potensi Mekanisasi Budidaya Tebu Lahan Kering di Kabupaten Merauke, Provinsi Papua (Mechanization Potency of Dry Land Sugarcane Cultivation at Merauke County, Papua Province) - Gatot Pramuhadi (Perum BULOG, 2013)
Penelitian bertujuan untuk mengkaji potensi mekanisasi budidaya tebu lahan kering di Kabupaten Merauke, Propinsi Papua. Hasil kajian menunjukkan bahwa tanah di wilayah survey (Domande dan Kaliki) sangat potensial dalam menopang operasional mesin untuk pekerjaan pembukaan lahan, pembentukan lahan, dan penyiapan lahan sehingga tanah di wilayah survey berpotensi untuk aplikasi mekanisasi budidaya tebu lahan kering. Semua mesin (alat berat) merk Komatsu dan Caterpillar (ground pressure 0,26– 2,67 kgf/cm2) bisa dioperasikan di wilayah survey karena besar tahanan penetrasi tanah rata-rata hingga kedalaman 10 cm di lokasi survey sebesar 3,58 – 10,33 kgf/cm2. Tanah yang lebih dalam berpotensi memiliki densitas tanah maksimum lebih tinggi dibanding tanah di atasnya, sehingga perlu tindakan pengolahan tanah optimum lebih dari 40 cm. Nilai permeabilitas tanah rata-rata semakin turun pada lapisan tanah yang semakin dalam, yaitu dari 0,2625 mm/jam menjadi 0,0122 mm/jam dan dari 0,2567 mm/jam menjadi 0,0312 mm/jam. Tanah di wilayah survey tergolong tanah berdrainase buruk karena waktu peresapan air rata-rata ke dalam tanah lebih dari 30 hari, sehingga perlu rekayasa untuk membuat saluran-saluran drainase dalam dan kolam penampungan air yang bisa dimanfaatkan tanaman tebu lahan kering pada musim kering (kemarau). Waktu tersedia untuk operasional mesin sebanyak ± 14 hari/bulan dan sesuai untuk budidaya tanaman tebu lahan kering.The objective of the research was to study mechanization potency of dry land sugarcane cultivation in Merauke County, Papua Province with indicators were ability of machines to travel across soil surface on natural or field existing of soil physical and mechanical conditions, and ability of dry land sugarcane to grow and make interaction with new growing environment from planting up to harvesting. Results of the research showed that soil in surveyed region (Domande and Kaliki) were very potential in machines operational supporting for land clearing, land forming, and land preparation so that it had potency for mechanization application of dry land sugarcane cultivation. All machines with trade mark of Komatsu and Caterpillar (ground pressure of 0.26 – 2.67 kgf/cm2) could be operated in surveyed regions because the amount of average soil penetration resistance up to 10 cm depth in the surveyed regions were 3.58 – 10.33 kgf/cm2. Deeper soil layers possessed higher maximum soil dry bulk density than above soil layer, so that it needed optimum soil tillage action more than 40 cm from soil surface. Average soil permeabilities decreased on the deeper soil layers possessed higher maximum soil dry bulk density than above soil layer, so that it needed optimum soil tillage action more than 40 cm from soil surface. Average soil permeabilities decreased on the deeper soil layer, which were from 0.2625 mm/hour became 0.0122 mm/hour and from 0.2567 mm/hour became 0.0312 mm/hour. Soils in surveyed regions were categorized as bad drainage soil because it need average infiltration time more than 30 days, so that it need engineering application to make deep drainage canals and water ponds which can be took advantage by plant during draught season. Operational available time for machines operation was ± 14 days/month and suitable for dry land sugarcane cultivation.